Extension Management in Animal Resource development for improvement in Rural economy: a few issues - D. Sen, (Journal of Agricultural Extension Management, 2025)
India is very rich in respect to its holding of livestock population. Fifteen per cent of the global cattle population sustains on merely 2.5 per cent of world's land resources, being held by India. A very high proportion of the country's population depends, either directly or indirectly, on livestock resources for maintaining their livelihood. More than 73 per cent of rural households in the country maintain livestock as a source of subsidiary income generation, which account for upto 40 per cent of their annual income. More importantly, almost 80 per cent of the 479 million livestock, including 197 million cattle and 88 million buffaloes in the country are held by small and marginal farming households, thereby making the livestock rearing an inexplicable component of their livelihood system. Again, more than 72 per cent rural mulch animal holding households own only one or two animals (Negi, 2002). Thus, any attempt of developing the livestock sector of the country should, essentially focus its attention on the resource poor segment of the rural society and thereby make the programme relevant to their conditions also